2020
DOI: 10.1093/sleep/zsaa110
|View full text |Cite
|
Sign up to set email alerts
|

Gestational sleep deprivation is associated with higher offspring body mass index and blood pressure

Abstract: Study Objectives The objective of this study was to evaluate the association between gestational sleep deprivation and childhood adiposity and cardiometabolic profile. Methods Data were used from two population-based birth cohorts (Rhea study and Amsterdam Born Children and their Development study). A total of 3,608 pregnant women and their children were followed up until the age of 11 years. Gestational sleep deprivation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
0
20
2
2
Order By: Relevance
“…This study also showed that the association was more pronounced in girls than boys [130], which is in contrast with mice study. Along with sleep deprivation, the authors of this study also encourage further studies on sleep quality during pregnancy [130]. Also, there is a need for an official sleep recommendation for pregnant women; however, based on the findings of this study, sleep deprivation (i.e., sleep duration of 6 h and less) has to be avoided at any stage of pregnancy [130].…”
Section: Epigenetics Of Sleep Disturbances and Metabolic Consequencescontrasting
confidence: 99%
See 4 more Smart Citations
“…This study also showed that the association was more pronounced in girls than boys [130], which is in contrast with mice study. Along with sleep deprivation, the authors of this study also encourage further studies on sleep quality during pregnancy [130]. Also, there is a need for an official sleep recommendation for pregnant women; however, based on the findings of this study, sleep deprivation (i.e., sleep duration of 6 h and less) has to be avoided at any stage of pregnancy [130].…”
Section: Epigenetics Of Sleep Disturbances and Metabolic Consequencescontrasting
confidence: 99%
“…Data from two European cohorts were used to accommodate diversity in ethnic and demographic characteristics, and it was found that gestational sleep deprivation might be associated with an increased risk of overweight and higher blood pressure in offspring till the age of 11 years [130]. This study also showed that the association was more pronounced in girls than boys [130], which is in contrast with mice study. Along with sleep deprivation, the authors of this study also encourage further studies on sleep quality during pregnancy [130].…”
Section: Epigenetics Of Sleep Disturbances and Metabolic Consequencescontrasting
confidence: 82%
See 3 more Smart Citations